An inquiry into EFL teachers' beliefs concerning effective teaching, student learning and development - Gülten Koşar; Sevda Doğan Dolapçıoğlu (Journal of Pedagogical Research, 2021)
How teaching could be conducted effectively and consequently student learning could be enhanced presumably vary from teacher to teacher, arising from a variety of such factors as the conditions in the workplace, teachers' year of teaching experience and their prior schooling experiences. In this regard, English-as-a-foreign-language (EFL) teachers' (EFLTs) beliefs about quality teaching leading to facilitated student learning are also highly likely to be divergent. This survey research aims to add to the growing literature on teacher beliefs via unveiling EFLTs' (N = 520) beliefs regarding effective teaching in general and effective EFL teaching in particular, student learning and development, and the probable changes that may occur in their beliefs according to the year of their teaching experience and the level of education they teach. The results revealed that the EFLTs held strong beliefs with respect to the effect of constructivist and humanistic concepts on effective teaching and student learning, and believed implementing communicative approach and conducting interactive activities induced effective EFL teaching and student learning. The findings also indicated that there existed statistically significant differences in EFLTs' beliefs concerning constructivist concepts and EFL teaching practices according to the year of their teaching experience.